2022
DOI: 10.37567/ijgie.v3i1.1052
|View full text |Cite
|
Sign up to set email alerts
|

Teacher Performance, Organizational Culture, Compensation, and Spiritual Leadership: A Literature Study

Abstract: This study aims to explore and analyze theories of organizational culture, compensation, and spiritual leadership and how they affect performance based on preliminary studies. The method used in this study is literature study. Relevant data is searched through books and scientific journals of international and national repute published on Google Scholar. The steps of data analysis consist of editing, organizing, and making conclusions. The results of the study reveal that there is a significant impact of organ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 27 publications
(31 reference statements)
0
2
0
Order By: Relevance
“…A spiritual leader always contributes to the institution and all people (Saripudin & Rosari, 2019) and has a significant influence on teachers' performance (Supriyanto & Ekowati, 2020;Mariyanti et al, 2020;Syahid et al, 2022); their satisfaction (Azazz & Elshaer, 2021) and affective commitment (Pradesa & Tanjung, 2021). He always works to contribute his best while he has the opportunity and ability to dedicate himself to God and others.…”
Section: Resultsmentioning
confidence: 99%
“…A spiritual leader always contributes to the institution and all people (Saripudin & Rosari, 2019) and has a significant influence on teachers' performance (Supriyanto & Ekowati, 2020;Mariyanti et al, 2020;Syahid et al, 2022); their satisfaction (Azazz & Elshaer, 2021) and affective commitment (Pradesa & Tanjung, 2021). He always works to contribute his best while he has the opportunity and ability to dedicate himself to God and others.…”
Section: Resultsmentioning
confidence: 99%
“…Pratama et al (2020) studies on transformational leadership have demonstrated its positive influence on organizational outcomes, including employee satisfaction and performance. Previous research has explored various aspects of leadership, compensation, and teacher performance in educational settings Sutanto et al (2022); Syahid et al (2022); Pratolo et al (2021); Mastur et al (2022); Widayadi et al (2021). Because, of course, this research is not the first scientific work, and based on the limitations of these studies, this paper was written.…”
Section: Introductionmentioning
confidence: 99%